(untitled) - Jones, Leo (Cambridge, UK, 1997)
Functions of American English is for adults and young adults at high intermediate and advanced levels who need to learn to communicate effectively with the English they have acquired.
Keywords: Americanisms,English language; Conversation and phrase books